2019
DOI: 10.1111/crj.13030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise‐induced dyspnoea on the aspiration rate among patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: Purpose To use radionuclide imaging to investigate silent aspiration among patients recovering from an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). We also evaluated the effects of exercise‐induced dyspnoea on silent aspiration in COPD patients. Patients and methods Recovering AECOPD patients admitted to the First Affiliated Hospital of Guangzhou Medical University between December 2013 and December 2015 were selected for the radionuclide aspiration test along with healthy volunteers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These factors include ventilation, cardiovascular, musculoskeletal, severe pain,obesity or malnutrition, mental disorders, sleep disorders, etc. Although activity restriction in COPD is influenced by multiple factors, dyspnoea associated with acute disorders of dynamic ventilatory mechanics is a major symptom of restricted exercise in most COPD patients, leading to the occurrence of kinetophobia, thus causing patients to fear lung rehabilitation training, affecting the recovery of the disease and improvement of lung function (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors include ventilation, cardiovascular, musculoskeletal, severe pain,obesity or malnutrition, mental disorders, sleep disorders, etc. Although activity restriction in COPD is influenced by multiple factors, dyspnoea associated with acute disorders of dynamic ventilatory mechanics is a major symptom of restricted exercise in most COPD patients, leading to the occurrence of kinetophobia, thus causing patients to fear lung rehabilitation training, affecting the recovery of the disease and improvement of lung function (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that the transfer of microflora from the stomach and/or throat to the lower respiratory tract is one of the major pathogenic mechanisms in patients with severe pneumonia. Moreover, relevant literature has reported the occurrence of silent aspiration in recovered AECOPD patients, with a significantly higher incidence rate compared to age-matched healthy volunteers [ 15 ]. Additionally, literature supports the notion that microaspiration under the glottis can impact lung microflora [ 16 ].…”
Section: Trends In Microbial Dynamics In Lung Of Patients With Septic...mentioning
confidence: 99%